Public-debt management: The Brazilian experience - Helder Ferreira de Mendonça; Viviane Santos Vivian (CEPAL Review, 2008)
This paper analyses public-debt management in Brazil, and considers the main recent theoretical models and the possible effect that the strategy adopted by the Treasury from 1999 onwards could have on the base interest rate. The findings show that the public-debt-management strategy adopted by Brazil was based on the recommendations of Calvo and Guidotti (1990). The average maturity of public debt, the proportion of shares linked to the Special System of Clearance and Custody (SELIC) and the public-debt-to-GDP ratio all play a significant role in determining the base interest rate. Government efforts to restructure public-debt maturities and reduce the negative effect on the interest rate are key in this regard.